Patient-specific computational fluid dynamics of femoro-popliteal stent-graft thrombosis. (December 2020) - Conti, Michele; Ferrarini, Anna; Finotello, Alice; Salsano, Giancarlo; Auricchio, Ferdinando; Palombo, Domenico; Spinella, Giovanni; Pane, Bianca
Highlights: Patient-specific hemodynamics simulations are performed for femoro-popliteal artery in both straight- and bent-leg position. Size mismatch between overlapping stents induces intra-stent lumen discontinuity. Proximal stent has larger caliber, lower velocity, lower wall shear stress, and lower helicity than distal one. Intra-stent thrombosis has helical shape that correlates with helicity pattern computed by flow simulations. Leg bending increases of arterial tortuosity, reduces the flow velocity, promoting low wall shear stress. Abstract: Intra-stent thrombosis is one of the major failure modes of popliteal aneurysm endovascular repair, especially when the diseased arterial segment is long and requires overlapping stent-grafts having different nominal diameters in order to accommodate the native arterial tapering. However, the interplay between stent sizing, post-operative arterial tortuosity, luminal diameter, local hemodynamics, and thrombosis onset is not elucidated, yet. In the present study, a popliteal aneurysm was treated with endovascular deployment of two overlapped stent-grafts, showing intra-stent thrombosis at one-year follow-up examination. Patient-specific computational fluid-dynamics analyses including straight- and bent-leg position were performed. The computational fluid-dynamics analysis showed that the overlapping of the stent-grafts induces a severe discontinuity of lumen, dividing the stented artery in two regions: the proximal part, affected by thrombosis, is characterized by larger diameter, low tortuosity, low flow velocity, low helicity, and low wall shear stress; the distal part presents higher tortuosity and smaller lumen diameter promoting higher flow velocity, higher helicity, and higher wall shear stress. Moreover, leg bending induces an overall increase of arterial tortuosity and reduces flow velocity promoting furtherly the luminal area exposed to low wall shear stress.